The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3892/ijo.2015.3283
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of the plasminogen activator inhibitor type 1 is involved in degradation of extracellular matrix surrounding cervical cancer stem cells

Abstract: Abstract. The plasminogen activator (PA) system consists of plasminogen activator inhibitor type 1 (PAI-1), urokinase-type plasminogen activator and its receptor (uPA and uPAR). PAI-1 inhibits the activation of uPA (which converts plasminogen to plasmin), and is involved in cancer invasion and metastasis, by remodeling the extracellular matrix (ECM) through regulating plasmin. Cancer stem cells (CSCs) are a small subset of cells within tumors, and are thought to be involved in tumor recurrence and metastasis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…Hence, it is important to note that two of them – RRAD [ 40 ] and CDKN1A [ 41 ] were reported to affect the activation of stem cell factors OCT4, NANOG, and SOX2. Moreover, the activity of SERPINE1 was involved in the promotion of the stem cell-like phenotype of cancer cells [ 42 ]. Furthermore, IL4I1 expressed in tumor-associated myeloid cells was involved in immune evasion of cancer cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important to note that two of them – RRAD [ 40 ] and CDKN1A [ 41 ] were reported to affect the activation of stem cell factors OCT4, NANOG, and SOX2. Moreover, the activity of SERPINE1 was involved in the promotion of the stem cell-like phenotype of cancer cells [ 42 ]. Furthermore, IL4I1 expressed in tumor-associated myeloid cells was involved in immune evasion of cancer cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, we showed a new approach for cervical CSC research, and in that sense, we can conclude that iRCs are potentially useful. Indeed, we focused on the relationship between cervical CSCs and PAI-1 from the cytokine analysis data (Figure 5), and, using the conventional cervical cancer cell lines CaSki and SiHa, we have already shown that PAI-1 plays a role in the maintenance of the extracellular matrix surrounding cervical CSCs [46]. In addition, we found the discrepancies between extracellular HLA-G expression and intracellular HLA-G expression.…”
Section: Discussionmentioning
confidence: 93%
“…PGE 2 can increase mRNA and protein levels of PAI-1 by binding with EP1/EP3 receptor in rat ventricular fibroblasts, contributing to elevated fibrin deposition in aortic stenosis (Kassem et al 2014 ). However, Sato et al suggested that TM5275 (a small molecular inhibitor of PAI-1) can increase the collagenase activity of SiHa and CaSki cells (Sato et al 2016 ), implying that lower expression of PAI-1 benefits the ECM degration and cervical cancer migration. The latter study was in accordance with our study that silencing EP3 increased the production of PAI-1 and decreased the migration in HeLa and SiHa cells.…”
Section: Discussionmentioning
confidence: 99%
“…The latter study was in accordance with our study that silencing EP3 increased the production of PAI-1 and decreased the migration in HeLa and SiHa cells. Conflicting effects of PAI-1 on migration might due to the different distances of cervical cancer cells from basal membrane (Sato et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation